Potencial de crecimiento de la especie gmelina arborea roxb (melina) en el Sector El Cóndor Cantón Valencia. Periodo 2013 - 2015 - Balarezo Zambrano, Wilmer Heriberto (2016)
The growth potential species assessment Gmelina arborea Roxb (melina) was performed on two sources; Costa Rica and Ecuador, in the Condor Valencia canton. Provenances were established in February 2015, and analyzed by a completely randomized design (DCA) with two treatments and four repetitions; an initial spacing of 3 x 3 m. The variables studied were dasometric; commercial height, diameter, basal area, and volume increase trade volume. During periods 2013-2015 commercial statistically significant differences in height, diameter, basal area and commercial volume (Duncan, p <= 0,05) did not occur. Regression analysis shows that trees from Costa Rica have higher volumetric growth with 0,5302 m3 ha-1, in relation to trees showing provenance Ecuador 0,4098 m3 ha-1 at 10 years of projection. This research is important because it allowed identify sources of melina largest commercial timber volume increase in the Condor Sector of Valencia canton.